2020
DOI: 10.1039/c9dt02934f
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive and selective colorimetric probe based on a cycloruthenated complex: an Hg2+-promoted switch of thiophene coordination

Abstract: A cycloruthenated complex can be used as a colorimetric Hg2+-probe by an Hg2+-promoted switch to thiophene coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The ruthenium derived complex 85 (Figure 28) was reported for the colorimetric detection of Hg 2+ , where the coordination of mode of Ru 2+ to the C-atom is changed to S-atom with the addition of Hg 2+ (Figure 29). The Hg 2+ -prompted switch in coordination mode in 85 caused a color from dark red to light yellow, and the absorption band at 506 and 730 nm are gradually quenched with the sensitivity limit of 21 nM [110]. With the similar approach, the ruthenium complex based sensor 86 (Figure 28) was reported for the selective colorimetric detection of Hg 2+ .…”
Section: Colorimetric Sensorsmentioning
confidence: 90%
“…The ruthenium derived complex 85 (Figure 28) was reported for the colorimetric detection of Hg 2+ , where the coordination of mode of Ru 2+ to the C-atom is changed to S-atom with the addition of Hg 2+ (Figure 29). The Hg 2+ -prompted switch in coordination mode in 85 caused a color from dark red to light yellow, and the absorption band at 506 and 730 nm are gradually quenched with the sensitivity limit of 21 nM [110]. With the similar approach, the ruthenium complex based sensor 86 (Figure 28) was reported for the selective colorimetric detection of Hg 2+ .…”
Section: Colorimetric Sensorsmentioning
confidence: 90%
“…In another study, Li et al reported that a cyclometallated Ru(II) complex functionalized UCNPs for Hg 2+ detection in water [ 145 ]. By modifying the cyclometallated Ru(II) complex with a propylsulfonate-coupled hemi-cyanine, Ru(II) complex 32 was then produced as the chemosensor for Hg 2+ colorimetric analysis [ 146 ]. The Hg 2+ -initialized conversion of coordination from C to S atom led to a remarkable absorption and solution color change from dark red to light yellow.…”
Section: Ru(ii) Complex Chemosensors For Metal Ionsmentioning
confidence: 99%
“…[17,[26][27][28][29] According to the strong affinity of Hg 2+ with S atom, [30,31] we have synthesized several cycloruthenated 2-thienyl complexes that have been used to detect Hg 2+ with high sensitivity and selectivity. [15][16][17] Herein, a new cyclometalated ruthenium complex with a ditopic thienyl-NHC ligand was successfully synthesized and characterized (Scheme 1). The photophysical properties of Ru1 have been investigated in the absence and presence of some common metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Wade and Gabbaї reported the first example of cyclometalated ruthenium complex in sensing CN À and F À . [12] Up to now, only several cyclometalated ruthenium complexes have been successfully designed and used to detect some specific ions such as HSO 3 À , [13] NO 2 À , [14] and Hg 2+ , [15][16][17] which exhibit excellent spectral and color changes as well as satisfied sensitivity and selectivity. Hence, developments of new cycloruthenated complexes as probes to some specific ions are still interesting and attractive due to their extraordinary performances that have been reported before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation